Spontaneous Coronary Artery Dissection in a Patient with a Family History of Fatal Ascending Aortic Dissection: Case Report and Discussion of Diseases Causing Both Presentations - George Joy; Hany Eissa (Case Reports in Cardiology)
Background. Spontaneous coronary artery dissection (SCAD) is a rare cause of acute coronary syndrome (ACS). Aortic dissection and SCAD share common aetiologies such as a fibromuscular dysplasia (FMD), Marfan, Ehlers Danlos, and more rarely systemic lupus erythematosus and Loeys-Dietz; however, SCAD has never been known to have a familial association with aortic dissection. Case Summary. This case report describes a 48-year-old woman suffering from SCAD who had a mother who died from ascending aortic dissection in her 50s. Discussion. This is the first case report to our knowledge of a patient with SCAD with a first-degree relative with aortic dissection. Our case is interesting in that it shows that if predisposition to arterial dissection was inherited from mother to daughter, one of them suffered an extremely rare manifestation of their underlying disease. It also shows that a high index of suspicion is needed for SCAD in the presence of a patient with ACS and a family history of dissection elsewhere in the arterial tree.